Pentingnya Peran Etika Komunikasi Dalam Membentuk Sikap Toleransi dan Mencegah Terjadinya Konflik di SMK Negeri 6 Sukoharjo : Penelitian - Muh Zaenal Abidin; Melati Sahlita; Muhammad Yazid Mubarok; Wahyuning Chumaeson (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Communication ethics plays a crucial role in multicultural school environments like SMK Negeri 6 Sukoharjo, where cultural diversity and digital media use are prone to verbal conflicts and misunderstandings. This study aims to analyze the implementation of communication ethics socialization and its contribution to students' tolerance attitudes and conflict prevention. Employing a qualitative descriptive approach, the population includes students from grades X-XII and teachers at SMK Negeri 6 Sukoharjo, with a purposive sample of 30 students and 5 BK/PKn teachers. Instruments comprise semi-structured interview guides, observation sheets, and documentation, analyzed via Miles and Huberman's interactive model with triangulation. Findings reveal increased awareness of polite language, empathy, and emotion control post-socialization, supported by participatory methods. The conclusion states that socialization effectively strengthens tolerance when integrated sustainably into the curriculum, despite limitations in local scale.